Green Cloud Environmental Infrastructure (International Journal of Engineering and Computer Science, 2017)
We are in an era of considering environmental resource constraints along with more IT goals. Environmental impact and power consumption are becoming crucial architectural systemic quality metrics. Saving energy is a much more complex architectural problem, requiring a coordinated array of tactics, from architectural power management capacity planning techniques to optimizing operational processes and facilities design. This paper concentrates on how cloud computing provide some interesting architectural constructs, some great potential from a monetary aspect, and a very real option to provide a more environmentally friendly computing platform. This paper also deals with the definition of reduced energy consumption which is influenced by reduced greenhouse gas emissions and reduced operational costs for the data center and business.